Population of pollination weevil, Elaeidobius kamerunicus (Coleoptera: Curculionoidea) at Ladang Rengam (Kulim Plantation Berhad) / Nurathirah Izhanny Mazlan - Mazlan, Nurathirah Izhanny (Faculty of Plantation and Agrotechnology, 2019)
Pollination weevil Elaeidobius kamerunicus was introduced to the oil palm regions of Asian and Pacific early 1980. Pollination weevil had become the most important indicator for the formation of fruit bunch. The population of pollination weevil, Elaeidobius kamerunicus might be fluctuated due to the several factors and may affect the yield production of oil palm in Malaysia. The study was conducted to determine the mean population of pollination weevil on male inflorescence at Ladang Rengam, Johor, Malaysia from July to November 2018 respectively. A total of three spikelets from top, middle and below section of anthesising male inflorescence were randomly selected to data collection, the each section from male inflorescence were cut off and put into transparent bag to calculate the weevils. The sampling was randomly taken at each plot (4 plots) with three replications. The mean population of E. kamerunicus (number of individual) was 12 weevils per spikelet with the highest recorded about 111 number of individual (E. kamerunicus) per spikelet. The population pollination weevil, Elaeidobius kamerunicus in Ladang Rengam Johor is well establish with average 26707 per hectare. Based on previous researches, the number of weevil recorded showed that this palm oil plantation has an adequate number of pollinator for pollination activity. These findings will assist to further study the mean population of pollination weevil per ha with the fruit set and fruit bunch ratio.